Interferon (IFN)-λ Takes the Helm: Immunomodulatory Roles of Type III IFNs - Zanoni, Ivan; Granucci, Francesca; Broggi, Achille (Frontiers in Immunology, 2017)
Type III interferons (IFNs) (or IFN-λ) are the latest addition to the interferon family. Even though they share little protein homology with type I interferon, both exhibit remarkable functional similarities: each can be induced in response to viral infections, and both lead to Janus Kinases (JAKs) and signal transducer and activator of transcription (STATs) activation. The JAK/STAT pathway induces antiviral responses and interferon-stimulated gene (ISG) transcription. However, despite the similarities in their effector functions with type I interferons, IFN-λ also has a non-redundant role in protecting barrier organs: epithelial cells preferentially produce IFN-λ rather than type I interferons; and interferon lambda receptor 1 (IFNLR1), the specific receptor for IFN-λ, is highly expressed on cells of epithelial lineage. Thus far, IFN-λ has been considered mainly as an epithelial cytokine, which restricts viral replication in epithelial cells and constitutes an added layer of protection at mucosal sites. However, it is now increasingly recognized that IFNLR1 is expressed broadly, and that immune cells such as neutrophils and dendritic cells also respond to IFN-λ. Moreover, in many in vivo models, IFN-λ modulates immune cell functions and thereby configures itself less as a cytokine that is only specific to the epithelium, and more as a cytokine that directly controls the inflammatory response at mucosal sites. Here we critically review the recent literature on immune modulatory roles for IFN-λ, and distinguish between the direct and indirect effects of this interferon on immune cell functions in different inflammatory settings.